Historic Earthquakes for the Xianshuihe Fault Derived From Lake Mugeco in the Southeastern Margin of the Tibetan Plateau During the Past 300 Years - Liu, Liyuan; Yang, Jingxuan; Liu, Xingqi; Mao, Xin; Qin, Rong (Frontiers in Earth Science, 2022)
The lacustrine deposition with the continuity and chronological reliability is one of important archives to establish paleo-seismic sequences. In this study, sediment cores were obtained from Lake Mugeco located in Selaha section of Xianshuihe fault zone in southeastern margin of Tibetan Plateau. The chronology is established using 210Pb/137Cs and AMS14C dating results. Seismic events are identified based on sedimentary characteristics (color, density, grain size, etc.), organic matter content and high resolution XRF element scanning data for the past 300 years. There are three whitish turbidites in sediments of Lake Mugeco, which are characterized by high content of clay fraction and detrital elements (Ti, K, Ca, Rb, Sr, Zr), and low organic matter content. These three turbidites were formed in 1947-1956 A.D., 1913-1936 A.D., and 1641-1876 A.D., with dating errors, corresponding to large historical earthquakes of 1955 (Ms 7.5), 1932 (Ms 6), and 1725 (Ms 7) recorded in Selaha section of Xianshuihe fault zone. This study provides scientific evidence for further reconstructing longer temporal seismic events in Xianshuihe fault zone inferred from sediments of Lake Mugeco.